A comparative study on the psychological health status of pre-clinical medical students enrolled through different admission tests. Issue 6 (December 2020) - Yusoff, Muhamad S.B.
الملخص: أهداف البحث: أجريت هذه الدراسة في نهاية السنة الثانية لبرنامج كلية الطب لتقييم الاختلافات للحالة النفسية للطلاب المسجلين عن طريق المقابلات المتعددة الصغيرة والمقابلة الشخصية. طرق البحث: اعتمدنا دراسة مقطعية مقارنة على مجموعتين لطلاب ما قبل المرحلة السريرية الذين تم اختبارهم في اختبارين مختلفين للقبول. تم قياس مستويات التوتر، والقلق، والاكتئاب للطلبة عن طريق مقياس الاكتئاب، والقلق والتوتر. كما تم قياس مستوى إرهاقهم باستخدام مخزون كوبنهاجن للإرهاق. النتائج: لم تكن درجات التوتر، والقلق، والاكتئاب بين المقابلات المتعددة الصغيرة والمقابلة الشخصية مختلفة بشكل كبير. ولم تكن درجات العمل الشخصي وإرهاق الطالب بين المقابلات المتعددة الصغيرة والمقابلة الشخصية مختلفة بشكل كبير. لم يكن معدل انتشار التوتر (المقابلات المتعددة الصغيرة=٣٩٪، والمقابلة الشخصية=٣٦.٩٪)، والقلق (المقابلات المتعددة الصغيرة=٧٨٪، والمقابلة الشخصية=٦٧.٤٪)، والاكتئاب (المقابلات المتعددة الصغيرة=٤١٪، والمقابلة الشخصية=٣٦.٢٪)، والإرهاق (المقابلات المتعددة الصغيرة=٢٩٪، والمقابلة الشخصية=٣١.٩٪) بين مجموعات المقابلات المتعددة الصغيرة والمقابلة الشخصية مختلفة بشكل كبير. أظهرت هذه النتائج مستويات متشابهة من التوتر، والقلق، والاكتئاب، والإرهاق للطلبة في نهاية المرحلة ما قبل السريرية. الاستنتاجات: أظهرت هذه الدراسة الحالة الصحية النفسية المتشابهة لطلاب ما قبل المرحلة السريرية الذين تم تسجيلهم من خلال اختبارين مختلفين للقبول. وكان معدل انتشار التوتر، والقلق، والإرهاق، والإكتئاب بين طلاب الطب للمرحلة ما قبل السريرية مشابها للمعدل العالمي. وتشير هذه النتائج إلى أن كليات الطب يمكن أن تنظر في تنفيذ أيا من المقابلات المتعددة الصغيرة أو المقابلة الشخصية لتعيين المرشحين المناسبين للتدريب الطبي. Abstract: Objective: This study was conducted at the end of the second year of the pre-clinical program to assess differences in psychological status of students enrolled by multiple mini interview (MMI) and personal interview (PI). Methods: We adopted a comparative cross-sectional study on pre-clinical medical students who appeared in two different admission tests. The stress, anxiety, and depression levels of students were measured by the depression, anxiety, stress scale (DASS-21), and their burnout level was measured by the Copenhagen Burnout Inventory. Results: The stress, anxiety, and depression scores between MMI and PI were not significantly different ( p -value > 0.05). The personal, work and client burnout scores between MMI and PI were not significantly different ( p -value > 0.05). The prevalence of stress (MMI = 39%, PI = 36.9%), anxiety (MMI = 78%, PI = 67.4%), depression (MMI = 41%, PI = 36.2%) and burnout (MMI = 29%, PI = 31.9%) between MMI and PI cohorts was not significantly different ( p -value > 0.05). These results showed similar levels of stress, anxiety, depression, and burnout in students at the end of the pre-clinical phase. Conclusions: This study showed similar psychological health status of the pre-clinical students who were enrolled by two different admission tests. The prevalence of stress, anxiety, burnout, and depression among the pre-clinical medical students was comparable to the global prevalence. The results indicate that medical schools can consider implementing either MMI or PI to recruit suitable candidates for medical training.